The Effectiveness of Investing into the Innovative Human Capital: Assessment of Students in Kazan - I Z Garafiev (RUDN journal of Sociology, 2012)
This article analyzes the assessment of the effectiveness of investing into the innovative human capital by the students of Kazan. The effectiveness of investing into the human capital was estimated at two levels: potential and real. The results suggest an overestimation by the respondents of the potential level of investment: the students overestimate their readiness to work in their specialty, which adversely affects the formation of their criteria for evaluating the effectiveness of investing into their own human capital.